Activation of the NFκB signaling pathway in IL6+CSF3+ vascular endothelial cells promotes the formation of keloids - Liu, Delin; Zhang, Yidi; Zhen, Lisha; Xu, Rong; Ji, Zhenling; Ye, Zheng (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Background: Keloid is a disease caused by abnormal proliferation of skin fibres, the causative mechanism of which remains unclear. Method: In this study, endothelial cells of keloids were studied using scRNAseq combined with bulk-RNAseq data from keloids. The master regulators driving keloid development were identified by transcription factor enrichment analysis. The pattern of changes in vascular endothelial cells during keloid development was explored by inferring endothelial cell differentiation trajectories. Deconvolution of bulkRNAseq by CIBERSORTX verified the pattern of keloidogenesis. Immunohistochemistry for verification of the lesion process in keloid endothelial cells. Results: The endothelial cells of keloids consist of four main cell populations (MMP1+ Endo0, FOS+JUN+ Endo1, IL6+CSF3+Endo2, CXCL12+Endo3). Endo3 is an endothelial progenitor cell, Endo1 is an endothelial cell in the resting state, Endo2 is an endothelial cell in the activated state and Endo0 is an endothelial cell in the terminally differentiated state. Activation of the NFΚB signalling pathway is a typical feature of Endo2 and represents the early skin state of keloids. Conclusion: We have identified patterns of vascular endothelial cell lesions during keloidogenesis and development, and have found that activation of the NFΚB signalling pathway is an essential feature of keloid formation. These findings are expected to contribute to the understanding of the pathogenesis of keloids and to the development of new targeted therapeutic agents for the lesional characteristics of vascular endothelial cells.